Successful Whole Genome Sequencing-guided Treatment of Mycoplasma hominis Ventriculitis in a Preterm Infant. Issue 7 (July 2019) - Scaggs Huang, Felicia A.; Mortensen, Joel; Skoch, Jesse; Andersen, Heidi; Staat, Mary Allen; Schaffzin, Joshua K.; Haslam, David B.
Abstract : We report a case of Mycoplasma hominis ventriculitis in a preterm neonate that was successfully identified with 16S ribosomal RNA sequencing and whole genome sequencing after failure to detect the pathogen with conventional diagnostic methods. The infant required doxycycline with subsequent clearance of the infection and no evidence of drug toxicity.